Structural modulation in potassium birnessite single crystals. Issue 4 (5th January 2021) - Kulish, Liliia D.; Nukala, Pavan; Scholtens, Rick; Uiterwijk, A. G. Mike; Hamming-Green, Ruben; Blake, Graeme R.
Abstract : The largest single crystals of potassium birnessite thus far reported are grown. The structure is studied at atomic resolution. Mn 3+ /Mn 4+ charge ordering, structural modulation and stacking faults are found. Abstract : We report on the growth of single-crystal potassium birnessite (K0.31 MnO2 ·0.41H2 O) and present both the average and local structural characterization of this frustrated magnetic system. Single crystals were obtained employing a flux growth method with a KNO3 /B2 O3 flux at 700 °C. Single-crystal X-ray diffraction revealed an average orthorhombic symmetry, with space group Cmcm . A combination of high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) with atomic resolution energy dispersive X-ray spectroscopy (EDS) demonstrated the layered structure of potassium birnessite with manganese-containing planes well separated by layers of potassium atoms. MnO6 octahedra and the K/H2 O planes were clearly imaged via integrated differential phase contrast (iDPC) STEM. Furthermore, iDPC-STEM also revealed the existence of local domains with alternating contrast of the manganese oxide planes, most likely originating from charge ordering of Mn 3+ and Mn 4+ along the c -axis. These charge-ordered domains are clearly correlated with a reduction in the c -lattice parameter compared to the rest of the matrix. The insight gained from this work allows for a better understanding of the correlation between structure and magnetic properties.